Synergistic antibacterial effects of reuterin and catechin against Streptococcus mutans. (March 2021) - Zhang, Guofang; Tan, Ying; Yu, Tianshu; Wang, Sitong; Liu, Libo; Li, Chun
Abstract: Reuterin is a broad-spectrum antimicrobial agent widely used to control pathogenic bacteria. Antimicrobial properties of catechin have been well described. However, no information is available regarding their combination effects. The aim of the present study is to evaluate the antibacterial effects of reuterin and catechin alone or in combination against Streptococcus mutans ( S. mutans ). We found a clear synergistic effect of reuterin in combination with catechin on inhibiting growth of S. mutans . Combined treatment with reuterin and catechin resulted in reduced biofilm biomass and water-insoluble glucan content, and visibly damaged the biofilm structure. Moreover, the expression of biofilm-associated genes was significantly down-regulated after exposure to the combination. Our results demonstrate that the combination of reuterin and catechin exhibits synergistic antimicrobial activity against S. mutans by repressing growth, biofilm formation, water-insoluble glucan production, and virulence genes expression. These findings support this novel combination can be used as a natural antibacterial agent for the prevention of oral diseases. Highlights: Combination of reuterin and catechin excited a synergistic antibacterial effect. The combination synergistically inhibited biofilm formation and development. The combination remarkably altered S. mutans biofilm structures. The combination resulted in down-regulation of virulence-related genes expression.